2024
DOI: 10.5114/pjr.2024.134817
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning in ovarian cancer diagnosis: a comprehensive review of various imaging modalities

Mohammad Hossein Sadeghi,
Sedigheh Sina,
Hamid Omidi
et al.

Abstract: Ovarian cancer poses a major worldwide health issue, marked by high death rates and a deficiency in reliable diagnostic methods. The precise and prompt detection of ovarian cancer holds great importance in advancing patient outcomes and determining suitable treatment plans. Medical imaging techniques are vital in diagnosing ovarian cancer, but achieving accurate diagnoses remains challenging. Deep learning (DL), particularly convolutional neural networks (CNNs), has emerged as a promising solution to improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 83 publications
0
0
0
Order By: Relevance
“…Similarly, it demonstrated the viability of employing CNNs to detect pulmonary nodules in chest radiographs, with good sensitivity and specificity in identifying malignant nodules. MH Sadeghi et al [19]. researchers have investigated the use of CNNs in conjunction with other imaging modalities, such as computed tomography (CT) and positron emission tomography (PET), to increase the accuracy of lung nodule identification and classification.…”
Section: Related Workmentioning
confidence: 99%
“…Similarly, it demonstrated the viability of employing CNNs to detect pulmonary nodules in chest radiographs, with good sensitivity and specificity in identifying malignant nodules. MH Sadeghi et al [19]. researchers have investigated the use of CNNs in conjunction with other imaging modalities, such as computed tomography (CT) and positron emission tomography (PET), to increase the accuracy of lung nodule identification and classification.…”
Section: Related Workmentioning
confidence: 99%
“…Deep learning (DL) can quantitatively analyze of medical images and has been applied in the field of oncology (Taddese et al 2024 ). Several studies demonstrated that DL can improve the diagnosis, predict treatment responses, and progression-free survival of patients with ovarian tumors (Arezzo et al 2022 ; Boehm et al 2022 ; Na et al 2024 ; Sadeghi et al 2024 ; Yao et al 2021 ). Compared with traditional imaging diagnosis by radiologists, the DL method can improve the accuracy and reduce the bias of diagnosis results (Chen et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%